ANALISIS PENERAPAN GREEN ACCOUNTING SESUAI PSAK 57 DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS PERUSAHAAN PERTAMBANGAN (Studi Empiris pada Perusahaan yang Listing di Bursa Efek Indonesia tahun 2014-2018) - Anggi Choirun Nisa; Anik Malikah; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2020)
The existence of environmental problems due to the company's operations, and the demands of several parties who ask that the company can be responsible for each company's operations, from where the accounting clean up and start applying green accounting. This study aims to see how the influence of the adoption of green accounting in accordance with PSAK 57 and environmental performance on profitability. The companies sampled in this study are mining companies listed on the Indonesia Stock Exchange that have implemented green accounting in accordance with PSAK 57 and who have been registered in the PROPER environmental performance assessment program by analyzing the annual report for the period 2014 - 2018. The method in this study uses the SPSS program 21. The results of this study indicate that the application of green accounting in accordance with PSAK 57 and environmental performance significantly influence the profitability of companies with an influence of 48.6%.Keywords: Environmental Problems, Green Accounting, PSAK 57, Environmental Performance